TRAINING ON DESIGNING INTERACTIVE LEARNING MEDIA-BASED AI (ARTIFICIAL INTELLIGENCE) AT SMPN 1 PLUMBON - Jajang Rahmatudin; Siti Musyarofah; Syifa Fijri Arrofilah; Tiwi Widyawati; Hisyam Ahyani; Shoimatul Atifah (Jurnal Abdisci, 2024)
Abstract: SMPN 1 Plumbon is one of the public schools in Cirebon Regency. Based on the results of observations, SMPN 1 Plumbon already has facilities that support digital-based learning. Technology can help teachers be more creative in developing learning in the classroom. One way to expand learning in the school is by utilizing creative learning media so students can be more active. Learning media can facilitate the achievement of specific learning goals. Based on this description, Community Service (PKM) was carried out on learning media in the form of a learning media workshop with the theme "AI-Based Learning Media Design Training (Artificial Intelligence)." This activity aims to train teachers in utilizing technology by creating AI-based interactive learning media (Artificial intelligence). The "AI-Based Learning Media Design Training (Artificial Intelligence)" was implemented on May 17, 2024, at SMPN 1 Plumbon with the resource person Mr. Jajang Rahmatudin, M.Pd. The training was carried out at 13.00, the training activity for AI-based interactive learning media design (Artificial intelligence). It began with the brief provision of material by the resource persons. After the provision of the material, the trainees were invited to try to design AI-based interactive learning media (Artificial intelligence) directly on the spot. The resource person explained the steps that must be taken, and then the participants followed the directions. Students help assist participants who have difficulties creating learning media. The implementation of the training went smoothly and well, and the trainees looked enthusiastic during the training activities.